Impact of Nurse-led Educational Intervention on Knowledge and Attitude regarding Mothercraft among Primimother - Chellapandian, Poongodi; M, Anuradha.; Padmanaban, Padmavathy; D, Padmapriya (Journal of Neonatal Surgery, 2025)
Antenatal examination refers to the systematic monitoring of a woman throughout her pregnancy. It encompasses both general and obstetrical assessments and plays a crucial role in identifying any abnormalities early on, ensuring the health and well-being of both mother and fetus. The primary goal of antenatal check-ups is to promote optimal maternal and fetal outcomes through timely and appropriate care. Objectives: The core objective of this study was to evaluate the knowledge of primigravida mothers regarding antenatal examinations and mothercraft, and to assess the effectiveness of a Video-Assisted Teaching Program (VATP) in enhancing their understanding through post-intervention knowledge scores. Methodology: A quantitative research approach using a pre-experimental one-group pre-test and post-test design was employed. The study used total enumeration sampling and included 60 antenatal mothers attending the OPD at PMCH&RI. Results: Prior to the intervention, 50% of participants demonstrated an inadequate level of knowledge, 70% had moderate knowledge, and only 4% possessed adequate understanding. Following the implementation of the VATP, the post-test results showed a significant improvement—75% of participants had adequate knowledge, 26% showed moderate knowledge, and only 4% remained at an inadequate level. The mean pre-test score was 14.82 ± 4.369, which increased to 22.80 ± 4.295 post-intervention. This improvement was found to be statistically significant (p ≤ 0.05). Conclusion: The findings reveal that many antenatal mothers initially lacked sufficient knowledge regarding antenatal examinations. However, the Video-Assisted Teaching Program proved to be an effective educational tool, significantly enhancing their understanding. The study highlights the importance of targeted educational interventions for primigravida mothers to support informed prenatal care and promote maternal and fetal health